The Phylogeny of Parasitic Hemiptera Using Multivariate Statistical Package Cluster Analysis - Astuti, Dwi Setyo; Nugroho, Murwanto Setyo (Universitas Muhammadiyah Surakarta, 2023)
Hemiptera is an Insecta with the characteristic of the forewing which has been modified as a